Numerical investigation of alternating-direction method for Poisson equation with weighted integral conditions - Štikonienė, Olga; Sapagovas, Mifodijus (Lietuvos matematikos rinkinys, 2010)
The present paper deals with a generalization of the alternating-direction implicit (ADI) method for a two dimensional Poisson equation in a rectangle domain with a weighted integral boundary condition in one coordinate direction. We consider the alternating direction method for a system of difference equations that approximates Poisson equation with weighed integral boundary conditions with the fourth-order accuracy. Sufficient conditions of stability for ADI method are investigated numerically. An analysis of results of computational experiments is presented.